"Globalization and the Quest for Quality Education Reforms" - A Case Study of the Challenges facing the Senior-Form English Language Teachers of a Private Secondary School in Hong Kong - Yeung, Portia Yuet Ping (2021)
The impacts of ‘Globalization’ are multi-dimensional. In the realm of education, driving for ‘quality’ in the delivery of educational service has become a global tide of educational reforms since the past 2 decades. Being a global city, Hong Kong is no exception and therefore not immune from this global wave of ‘quality education reforms’ either.